The Architectural Patronage of Ḍayfah Khātūn - Aridi, Julia (2023)
This thesis will conduct an analysis of the architectural patronage of Ḍayfah Khātūn, the queen regent of Aleppo between the years 1236 and 1243 C.E. It studies the architecture commissioned by her in light of the social and political changes in the Ayyubid Dynasty. The thesis goes on to discuss firstly Ayyubid Aleppo, secondly the architectural patronage of the Ayyubids including female patrons, and finally the architectural patronage of Ḍayfah khātūn; which consists of two buildings in Aleppo, Madrasat al Firdaws in the Maqamāt sector and Khanqah al Farāfra in the area under the citadel. It will come to show how the architecture commissioned by her was a means to exert and assert her power and stature. What makes her architectural patronage singular is that it is unlike prior female architectural patronage in Ayyubid Syria in terms of scale and location. Female patronage was not uncommon in the Seljuq and Ayyubid dynasties and primarily consisted of modest pious foundations and mausolea usually built at the outer edges of cities. By relying on Ayyubid historians, prior scholarship and a field visit, this thesis will show how the architecture commissioned by Ḍayfah Khātūn was utilized to cement her power and ensure the succession of her grandson. The buildings she commissioned are distinguished in that they feature new elements in Ayyubid architecture. They are located in prominent areas of the city and are of a relatively large scale. All of this and more comes to show the remarkable way in which Ḍayfah Khātūn was able to use architecture as a political tool to assert the power and status she attained as the queen regent of Aleppo.